Environmental Morale and Motivation - Bruno S. Frey; Alois Stutzer (Center for Research in Economics, Management and the Arts (CREMA), 2006)
This chapter discusses the role of environmental morale and environmental motivation in individual behavior from the point of view of economics and psychology. It deals with the fundamental public good problem, and presents empirical (laboratory and field) evidence on how the cooperation problem can be overcome. Four different theoretical approaches are distinguished according to how individuals' underlying environmental motivation is modeled. Specifically, we look at the interaction between environmental policy and environmental morale through the lens of cognitive evaluation theory (also known as crowding theory).
Keywords: D64; H41; Q50; Z13; 330; environmental morale; environmental policy; motivation crowding; pro-social preferences; public good problem